A systemic model of innovation for regional universities: Literature review [Un Modelo Sistémico de Innovación para Universidades Regionales: Revisión de Literatura] (2018)
Regional universities lack or have incipient innovation models. Currently the changes driven by technology and especially by the innovation generated from the technological application, make it necessary for universities to update their organizational structures in order to be relevant for the regions to which they belong. The objective of this work was to review the literature regarding systemic models of innovation that are relevant for regional universities, characterized by an under-entrepreneurial environment and with deficient support by the government. A systematic literature review (SLR) was carried out, this methodology guaranteed that the subject was evaluated in a rigorous, reliable and auditable manner. The main theoretical references found are: Knowledge networks, open innovation, hub and social innovation. In conclusion, an innovation model for regional universities is proposed based on the theoretical referents found and with a systemic approach that allows its evolution and adaptation to the region. This work is part of the doctoral thesis carried out by the author and which will initially have as a case study the Universidad del Magdalena and later its validation with other universities in Colombia. © 2018, Universidad del Zulia. All rights reserved.